Teamworking and Lean revisited: a reply to Carter et al. Issue 3 (4th February 2017) - Procter, Stephen; Radnor, Zoe
Abstract: This paper is a reply to Carter et al.'s response to an earlier paper of ours in this journal on the subject of teamworking under Lean in the UK public services . Our reply covers the following issues which Carter et al. have raised: the literature we used to structure our findings; the way in which we used concepts such as autonomy and teamworking; our research methods and approach; how Carter et al.'s newly available data on teamworking might be interpreted; and how data drawn from an official employee attitude survey might best be understood. On the basis of this, we conclude that Carter et al.'s paper fails to meet its objectives. On some things, the authors are simply wrong; on others, they grossly misrepresent our position; on still others, their interpretations are, at best, highly questionable.